Can we rely on public data as a source of information for cancer registry in developing countries? - Shahryar SEMNANI; Mohammad Javad KABIR; Sima BESHARAT; Nafiseh ABDOLAHI; Ahmad DANESH; Danyal ROSHANDEL (Turkish Journal of Gastroenterology, 2019)
-